Some physiological reactions of holstein cows at Jaboticabal, São Paulo - Salimos, Ermenson Peçanha; Rosa, Luis Claudio de Andrade; Andrade, Antonio Tadeu de; Mangerona, Aparecida Martinez; Pacheco, Maria Rita (Pesquisa Agropecuaria Brasileira, 2014)
Observations of the effect of air temperature and humidity on rectal temperature, respiratory rate, pulse rate, and haematocrit of Holstein cows were made in Jaboticabal, São Paulo, Brazil. The data were collected twice daily (7 a.m. and 2 p.m), two days per week, from March until May 1978, in normal management and feeding conditions. The results indicated that red-spotted Holstein cows had higher increases in respiratory rata, and their rectal temperatures were lower than that of black-spotted cows. Pulse rate, respiratory rate, and rectal temperature showed positive correlations with air temperature, but negative correlations with air humidity. The red-spotted cows presented also higher haematocrit values, probably due to their higher sweating rate.